Purchase Decision on Shopee E-Commerce Platform : The Influence of Product Quality, Brand Image, and Price through Trust as an Intervening Variable - Yozi Putri Sakinah; Putra, Muhammad Farrasky Delas (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine how much influence product quality, brand image and price have on purchasing decisions through trust as an intervening variable in Shopee e-commerce in the city of Padang. This study consists of three independent variables, namely product quality, brand image, and price and one dependent variable is purchasing decisions and the intervening variable trust. The analytical method used is path analysis. The data collection method in this study was using a questionnaire filled out by respondents, namely Shopee e-commerce users in the city of Padang. The results obtained based on the Partial Test (t test) obtained: a) there is a positive and significant effect of product quality on trust b) there is a positive and significant effect of brand image on trust, c) there is a positive and significant effect of price on trust, d) there is positive and significant influence of product quality on purchasing decisions, e) there is a positive and significant influence of brand image on purchasing decisions, f) there is a positive and significant influence of price on purchasing decisions. g) there is a positive and significant effect of trust on purchasing decisions, h) trust cannot mediate the effect of product quality on purchasing decisions, i) trust cannot mediate the influence of brand image on purchasing decisions, j) trust cannot mediate the effect of price on purchasing decisions